2015
DOI: 10.1103/physrevd.92.085009
|View full text |Cite
|
Sign up to set email alerts
|

Pulse shape dependence in the dynamically assisted Sauter-Schwinger effect

Abstract: While the Sauter-Schwinger effect describes nonperturbative electron-positron pair creation from vacuum by a strong and slowly varying electric field Estrong via tunneling, the dynamically assisted Sauter-Schwinger effect corresponds to a strong (exponential) enhancement of the pair-creation probability by an additional weak and fast electric or electromagnetic pulse E weak . Using the WKB and worldline instanton method, we find that this enhancement mechanism strongly depends on the shape of the fast pulse. F… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
120
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(131 citation statements)
references
References 49 publications
(70 reference statements)
11
120
0
Order By: Relevance
“…Preliminary investigations indicate that the world-line instanton method can also be applied to these more complex field profiles and that the general behavior of dynamically assisted Sauter-Schwinger effect persists. This will be the subject of future studies, see also [74].…”
Section: Jhep02(2016)164mentioning
confidence: 99%
“…Preliminary investigations indicate that the world-line instanton method can also be applied to these more complex field profiles and that the general behavior of dynamically assisted Sauter-Schwinger effect persists. This will be the subject of future studies, see also [74].…”
Section: Jhep02(2016)164mentioning
confidence: 99%
“…It was confirmed that the switch-on and -off effects may be very significant (see also Refs. [14][15][16]26]), especially if one considers a "sharp" time-or space-dependent switching function, which means that for 2D backgrounds both temporal and spatial dependences should be taken into account exactly which can be done with the aid of the technique developed. In this context it is worth noting that, according to Ref.…”
Section: Discussionmentioning
confidence: 99%
“…These results confirm that the switch-on and -off effects may play a very important role (see also Refs. [14][15][16]26]). Such effects with respect to the spatial finiteness of external fields will be discussed below.…”
Section: "Rectangular" Time-dependent Fieldmentioning
confidence: 99%
See 2 more Smart Citations